Pleomorphic adenoma: Choice of radiographic imaging modality - Computed tomography or magnetic resonance imaging? Illustration through a case report - Shalu Rai; Malik Rohit; Mandeep Kaur; Prabhat Mukul (Wolters Kluwer Medknow Publications, 2013)
Introduction: Pleomorphic adenoma (PA) is the most common benign neoplasm of the major salivary glands arising primarily from the parotid gland. Computed tomography (CT) is one of the primary imaging modalities used to assess the tumors of salivary glands. However, magnetic resonance imaging (MRI) may provide additional information over CT. Case Report: We report the case of a 60-year-old male with a slowly enlarging, well-defined, round, painless, non-fixated, rubber-like swelling over the left ramus region below the ear, measuring about 4 × 4.5 cm, covering the lower border of the mandible near the angle. A provisional diagnosis of PA was given and CT and MRI were used to study the lesion. Discussion: Through this case, which was suspected to have undergone malignant transformation because of indistinct margins and focal hypodense areas on CT but was later confirmed to be a benign salivary gland tumor on MRI, we illustrate the role of CT and MRI as diagnostic aids in PA and emphasize on what should be the choice of imaging modality for parotid tumors.